2020
DOI: 10.1021/acs.orglett.0c00024
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light Mediated Hydrosilylative and Hydrophosphorylative Cyclizations of Enynes and Dienes

Abstract: Described herein is a visible-light mediated intermolecular radical cyclization approach to access heterocycles. Heteroatom radicals, such as silicon and phosphorus atom radicals, were generated via direct hydrogen atom abstraction by the photoexcited catalyst species with hydro-silanes and phosphine oxides. The radical addition/cyclization/ HAT (hydrogen atom transfer) reaction sequences of 1,6-enynes and 1,6-dienes were highly efficient delivering the desired heterocycles in good yields.H eterocyclic scaffol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 69 publications
2
23
0
Order By: Relevance
“…(5)] [12] . Regarding the photocatalytic hydrosilylation of alkyne, Wang, Yao, [13] and Zhu [14] independently reported the synergistic use of photocatalyst and HAT catalyst to achieve the process [Eq. (6)].…”
Section: Methodsmentioning
confidence: 99%
“…(5)] [12] . Regarding the photocatalytic hydrosilylation of alkyne, Wang, Yao, [13] and Zhu [14] independently reported the synergistic use of photocatalyst and HAT catalyst to achieve the process [Eq. (6)].…”
Section: Methodsmentioning
confidence: 99%
“…Although significant progress has been achieved, the elaboration of the phosphorylation products of alkynes remains highly desirable. In 2017, Zhu et al [88] reported a silver-mediated radical 5-exo-dig cyclization of 2alkynylbenzonitrile with disubstituted phosphine oxides and H 2 O for the synthesis of phosphinylated 1indenones [Figure 55]. Multiple bonds, including C-P, C-C and C-O bonds, were successively constructed under atmospheric conditions.…”
Section: Radical Cascade Cyclization Phosphorylation Of Alkynesmentioning
confidence: 99%
“…However, the substrates were invariably limited to phenylsilanes or (TMS) 3 SiH with labile Si-H bonds (Scheme 1b). 11,[29][30][31][32][33][34][35] As pioneered by Fagnoni et al, 36 decatungstate was found to be an effective hydrogen atom transfer (HAT) photocatalyst for aromatic tertiary silanes activation (Scheme 1c). Nevertheless, only poor selectivities were observed for trialkylsilanes owing to the comparably high bond dissociation energies (BDEs) of Si-H and α-Si-C-H bonds (>92 kcal mol −1 ).…”
Section: Introductionmentioning
confidence: 99%